The Limiting Distribution of Production in Integrated Economies: Evidence from US States and EU Countries - Harry P. Bowen; Haris Munandar; Jean-Marie Viaene (Tinbergen Institute, 2005)
We show that in a fully integrated economy, in which there is free mobility of goods and factors, each member's share of total output will equal its shares of total stocks of productive factors (i.e., physical and human capital). We label this result the equal-share relationship. This relationship also holds in the presence of technological differences or costs of factor mobility among members if outputs or inputs are properly measured to reflect such differences or costs. The equal-share relationship is the limiting distribution of output and factors among members of a fully integrated economy, and it constraints the set of policies that can affect each member's relative growth within an integrated economy. We empirically examine for the equal-share relationship for alternative economic groups (i.e., US states, EU countries, Developing Countries and a World comprising 55 countries). Our findings indicate that the equal-share relationship holds strongly for US states, holds weakly for EU countries, but does not hold for Developing Countries or the World.
Keywords: E13; F15; F21; F22; O57; 330; Distribution of production; economic growth; economic convergence; factor mobiity; integrated economy; Wirtschaftsintegration; Internationale Faktormobilität; Entwicklungskonvergenz; Wirtschaftswachstum; EU-Staaten; USA